Relationship Of Competence (Knowledge, Attitude And Behavior) With Readiness To Apply Evidence-Based Practice In Nurse Profession Students - Fitroh Asriyadi; Arief Budiman (Green Publisher Indonesia, 2021)
Indonesia is currently in the 21st century where the learning process is developing, education is expected to be able to produce human resources capable of implementing programs and solving problems together in a wise, peaceful, and intelligent way. ). This research is a type of quantitative research with a correlational analytic design and uses a cross-sectional design where in this design the researcher wants to reveal the relationship between readiness to apply Evidence-Based Practice with knowledge, attitudes, and behavior in Nursing Professional Students, Muhammadiyah University of East Kalimantan. The population in this study is all students who will complete the academic program of S1 Nursing Science at the University of Muhammadiyah East Kalimantan and who will continue the profession of Ners at the University of Muhammadiyah East Kalimantan, and the number of samples in this researcher as many as 115, using the Non Probability Sampling method with sampling techniques used total sampling. This research will be carried out by the UMKT campus and Wahana learning of Ners professional practice. The conclusion of this study is the characteristics of respondents based on semester i.e. students are undergoing semester I education (one), the majority of respondents aged 17-25 years as many as 92 respondents, gender is mostly female as many as 76 respondents.